2006
DOI: 10.1249/00005768-200605001-00998
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Produced by a Conventional Therapeutic Ultrasound Unit Accelerates Fracture Repair

Abstract: Background and Purpose. A recent novel application of ultrasound therapy is the treatment of bone fractures. The aim of this study was to investigate the effect on fracture repair of ultrasound produced by a conventional therapeutic ultrasound unit as used by physical therapists. Subjects and Methods. Bilateral midshaft femur fractures were created in 30 adult male Long-Evans rats. Ultrasound therapy was commenced on the first day after fracture and introduced 5 days a week for 20 minutes a day. Each animal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 22 publications
0
27
1
2
Order By: Relevance
“…On the other hand, applications of therapeutic ultrasound are based on depositing ultrasound energy to specifically create effects. These can be mild and nondestructive, such as those generated for healing in physical therapy [22], or more extreme and destructive, such as thermal ablation of tumors [23]. There are presently a large range of therapeutic applications of ultrasound exposures based on the many ways that ultrasound energy can interact with cells and tissues [24].…”
Section: Diagnostic Us V Therapeutic Usmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, applications of therapeutic ultrasound are based on depositing ultrasound energy to specifically create effects. These can be mild and nondestructive, such as those generated for healing in physical therapy [22], or more extreme and destructive, such as thermal ablation of tumors [23]. There are presently a large range of therapeutic applications of ultrasound exposures based on the many ways that ultrasound energy can interact with cells and tissues [24].…”
Section: Diagnostic Us V Therapeutic Usmentioning
confidence: 99%
“…The range of applications for these exposures, which are thought to improve blood flow to the treated region, and hence increase the delivery of nutrients and oxygen as well as the removal of cellular wastes, include the relief of inflammation, muscle spasms and pain, in addition to accelerating healing and increasing range of motion [31]. Other applications include facilitating the repair of fractures [22], and preclinical studies have demonstrated how these exposures can accelerate the recovery of sciatic nerve injury [32]. Higher rates of energy deposition are presently being used to ablate solid tumors, such as prostate cancer [33] and uterine fibroids [34].…”
Section: Applications Of Therapeutic Ultrasoundmentioning
confidence: 99%
“…Os resultados obtidos neste estudo para o grupo não suspenso (G1) concordam com Carvalho e Cliquet Jr 20 , que, analisando a ação do US pulsado de baixa intensidade durante 20 dias consecutivos por 20 minutos diários na região proximal dos fêmures de ratas osteopênicas, evidenciaram melhora da arquitetura dos ossos (análise qualitativa), mas não do conteúdo mineral (análise quantitativa), supondo que a análise quantitativa não tenha apontado diferenças devido ao fato de existir grande quantidade de tecido neoformado, o qual ainda não está totalmente mineralizado. Os autores comentam que a duração do tratamento com US de baixa intensidade talvez não tenha sido suficiente para possibilitar a total mineralização das regiões estimuladas, o que não gerou alterações de forma quantitativa, fato que pode ter influenciado os resultados do presente trabalho, uma vez que usamos somente análise quantitativa, além de termos utilizado menor tempo de tratamento quando comparados com outros estudos [21][22][23] .…”
Section: Discussionunclassified
“…In basic research, it was reported osteoblast cell line were maturated and accelerated calcification by LIPUS stimulation [11][12][13] . Furthermore, it was clarified LIPUS exposure promotes healing process and increases bone mineral density by rat femurs fracture model 14,15) . It was also reported about the effect of LIPUS exposure for bone with titanium implant.…”
Section: Introductionmentioning
confidence: 99%